Психологічні аспекти інформаційного впливу під час воєнних дій в Україні - Жданова, І. В.; Zhdanova, I. V.; ORCID: http://orcid.org/0000-0002-6361-3029; Бондаренко, Л. О.; Bondarenko, L. O.; Велічко, А. В.; Velichko, A. V. (Габітус. - 2022. - Вип. 41. - С. 222-226, 2022)
Наведено огляд сучасних публікацій щодо інформаційно-психологічного впливу на особистість людини, її механізмів, стратегій, закономірностей, засобів, в тому числі – в інформаційній війні. Визначено поняття інформаційного впливу, його різновиди, відзначено маніпулятивний та сугестивний характер інформаційного впливу з боку ЗМІ, суб’єктів медіаресурсів.

The article provides an overview of modern publications on the informational and psychological impact on a person’s personality, its mechanisms, strategies, laws, and means, including information warfare. The concept of informational influence, its varieties, defined, the manipulative and suggestive nature of informational influence in mass media noted. It shown that the problem of the influence of the mass media on the personality during actual military operations in Ukraine is practically undeveloped today. The article presents the results of its own research, conducted with the help of an online survey, on the peculiarities of the psychological impact of war news on the personality and mental states of civilians during the war in Ukraine. It is shown that there is a significant psychological impact of information about military actions on the psyche of the majority of peaceful citizens. War news has an impact on people’s mental states, their well-being, cognitive processes, and future prospects. The dominant mental states of civilians at the beginning of the war were confusion, anxiety, and uncertainty. There is a significant immersion of people in information about war news at the beginning of the war, which gradually decreases over time to a more optimal level. The choice of telegram channels as a leading information resource, on the one hand, gives a certain freedom in the choice of topics and sources of information, on the other hand, it increases the level of suggestive influence in the most suggestible persons without being critical of this information. Socio-psychological adaptation to the life in the conditions of military operations takes place at the expense of reducing the time spent watching war news, developing the ability to identify fake information, developing tolerance for uncertainty, and restoring the continuity of life.

Представлен обзор современных публикаций относительно информационно-психологического влияния на личность человека, его механизмов, стратегий, закономерностей, средств, в том числе – в информационной войне. Определены понятия информационного влияния, его разновидности, отмечены манипулятивный и внушающий характер информационного влияния со стороны СМИ, субъектов медиаресурсов.
Psychological aspects of information influence during military operations in Ukraine
Жданова, І. В. Психологічні аспекти інформаційного впливу під час воєнних дій в Україні / Жданова І. В., Бондаренко Л. О., Велічко А. В. // Габітус. - 2022. - Вип. 41. - С. 222-226. - DOI: https://doi.org/10.32782/2663-5208.2022.41.39.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; інформаційний вплив; information influence; информационное влияние; психологічний вплив; psychological influence; психологическое влияние; психічні стани; mental states; психические состояния; воєнні дії; military actions; военные действия